Adenovirus Particles that Display the Plasmodium falciparum Circumsporozoite Protein NANP Repeat Induce Sporozoite-Neutralizing Antibodies in Mice - Palma, Christopher (2011)
Adenovirus particles can be engineered to display exogenous peptides on their surfaces by modification of viral capsid proteins, and particles that display pathogen-derived peptides can induce protective immunity. We constructed viable recombinant adenoviruses that display B-cell epitopes from the Plasmodium falciparum circumsporozoite protein (PfCSP) in the major adenovirus capsid protein, hexon. Recombinants induced high-titer antibodies against CSP when injected intraperitoneally into mice. Serum obtained from immunized mice recognized both recombinant PfCSP protein and P. falciparum sporozoites, and neutralized P. falciparum sporozoites in vitro. Replicating adenovirus vaccines have provided economical protection against adenovirus disease for over three decades. The recombinants described here may provide a path to an affordable malaria vaccine in the developing world.